FINITE ELEMENT ANALYSIS OF GUSSET PLATE CONNECTION DESIGN FOR COLD-FORMED STEEL FRAMES - Ng, Aloysius Yoke Khing; Lee, Yeong Huei; Ting, Tina Chui Huon; Tan, Cher Siang; Mohammad, Shahrin (Journal of Civil Engineering, Science and Technology, 2022)
The application of cold-formed steel sections has been extended from secondary members to primary structural members in recent years. This increases the use of gusset plate connections in cold-formed steel since it is a common connection used in steel structures. However, current design codes on connection design do not have a comprehensive method to consider the effects due to the buckling of the thin cold-formed steel sections. Therefore, it is important to develop a more accurate model to predict the capacity of cold-formed steel connections. This paper aims to propose an equation for gusset plate beam-to-column connection using finite element models. Finite element models have been developed and compared with existing test results. The failure mode and ultimate strength of the numerical models are similar to the experimental results. The validated finite element models are then used to study the effects of gusset plate thickness, effects of cold-formed steel section depth and thickness, and the effects of bolt size and spacings. Elastic and plastic stiffnesses are obtained from the developed models. The connection behavior followed a typical elastic-plastic curve according to the connection ductility and failure mode. An empirical model is developed from the finite element models to predict the joint behavior of gusset plate beam-to-column connection for cold-formed steel structures. AS 4600 may have underestimated the initial stiffness of the connection.